IMPLEMENTATION OF THE INDONESIA PINTAR (PIP) PROGRAM POLICY IN IMPROVING STUDENTS' ACCESS TO LEARNING AT SDN KALANGSURYA III & SDN SINDANGMUKTI II - Nurali, Nurali; Sauri, R. Supyan (Jurnal Konseling Pendidikan Islam, 2025)
This research was conducted at SD Negeri Kalangsurya III and SD Negeri Sindangmukti II, Karawang Regency, which are recipients of the Smart Indonesia Program (PIP). The implementation of the PIP policy in the field still faces a number of problems, such as mistargeting, delays in fund disbursement, and a lack of socialization. This study aims to find out, analyze, and evaluate the extent to which the implementation of PIP has succeeded in increasing access to education for students from underprivileged families and identify the supporting and inhibiting factors for its implementation. The research method used is a qualitative approach with the basis of George R. Terry's management theory, including planning, organising, implementing, and supervising, and Pierre Bourdieu's theory of access to education, which emphasises social, cultural, and habitus capital. The results showed that the program planning was systematic and involved various elements of the school, thus improving access to education. The organization was effective in expanding the reach of beneficiaries. Program implementation is strongly influenced by cross-party coordination and the implementing structure at the school level. Evaluation shows an increase in attendance and a decrease in dropout rates, although there are still constraints in terms of facilities, infrastructure and financing. Proposed solutions include technical training, specialized PIP supervisors, improved information technology facilities, and strengthened internal supervision.